Superior gluten structure and more small starch granules synergistically confer dough quality for high amylose wheat varieties - Li, Liqun; Liu, Zhenzhen; Li, Xu; Chu, Xiangnan; Yang, Weibing; Wang, Bingxin; Xie, Yanzhou; Li, Xuejun (Frontiers in Nutrition, 2023)
High amylose wheat (HAW) has potential health benefits but its dough structure is usually inferior. Wheat dough is a complex mixture and its structure is influenced by the physicochemical properties of gluten and starch. In this study, we investigated the starch granule development, gluten structure, starch properties, pasting, and thermal properties of flour, as well as the rheological properties of dough in wheat variety Xinong 836 with high amylose content (33.57%) and its parents. The results showed that Xinong 836 wheat starch contained more small starch granules, which was consistent with the microstructural results of starch granules in grain filling stage. Moreover, Xinong 836 wheat starch showed highest swelling power and water solubility. Importantly, the flour of Xinong 836 wheat had the highest protein content and wet gluten content and Xinong 836 wheat gluten showed highest -sheets content and disulfide bond content than its parents Zhengmai 7698 and Xinong 979, which conferring to more compact microscopic networks of dough, thereby contributing to the higher peak viscosity (PV), final viscosity (FV), and setback viscosity (SB) in the flour of Xinong 836. Our finding elucidated that the stability of gluten and properties of starch synergistically affected the pasting and thermal properties of the flour paste, and the presence of more small starch granules contributed to dough with a rather dense structure in high amylose wheat (HAW) Xinong836. Thus, superior gluten structure and more small starch granules have synergistic effects on enhancing the gluten–starch interaction, thereby contributing to better dough quality.